Relevansi Nilai Ritual Tolak Bala Lanting Bamban pada Pencegahan Dampak Pandemi COVID-19 - Kunti Vedanti Vedanti (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2020)
WHO declares COVID-19 as global endemic disease and impact to people around the world. It is causes complexity impact on human being and needs people awareness to take in hand it together, as well as Hindu religion society. Based on it phenomenon, this research is using descriptive qualitative method, to find the relevance value of The Ritual Tolak Bala Lanting Bamban to prevent the impact of COVID-19 endemic, that is; 1) the honest sacrifice value as a relevant value to build the action of social care on society, and 2) the value of reality of life based on Hinduism philosophy to build spiritual awareness and help calmness mind to face up the COVID-19 epidemic.